Mengevaluasi Efektivitas Praktik Audit Crytopcurrency dalam Teknologi Blockchain - Mohamad Rafki Nazar; Ananda Maulida; Ayra Ramadhina Zahra; Defina Damayanti; Wardanianti Sari Rahayu (Journal on Education, 2023)
In the current era of revolution 4.0, cryptocurrency has emerged, namely paying using digital. Technology that can be required in terms of recording and managing in various transactions. So that no third parties are needed in the transaction system and can cause more transparency in the financial transaction system. The purpose of the research study is to examine the influence in blockchain technology in audit practice. Research Methods use qualitative methods by searching for various existing literature sources. The results of this study have a positive impact on blockchain in cryptocurrency audit practices, in conducting validation and transactions there is ease in using technology and guarantees of reliable data and integrity and can obtain payments in a timely manner.